Proceedings of the 2002 ACM Conference on Computer Supported Cooperative Work 2002
DOI: 10.1145/587078.587124
|View full text |Cite
|
Sign up to set email alerts
|

Sharing and building digital group histories

Abstract: Organizations, families, institutions evolve a shared culture and history. In this work, we describe a system to facilitate conversation and storytelling about this collective past. Users explore digital archives of shared materials such as photographs, video, and text documents on a tabletop interface. Both the software and the interface encourage natural conversation and reflection. This work is an application of our ongoing research on systems for multiple, co-present users to explore digital collections. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…These explorations involved gathering data from a variety of sources including prior art HCI and CSCW literature describing existing digital tabletop systems, (e.g., Rekimoto and Saitoh, 1999;Streitz et al, 1999Streitz et al, , 2001; de Bruijn and RUSSELL KRUGER ET AL. Spence, 2001;Deitz and Leigh, 2001;Hancock and Booth, 2004;Shen et al, 2001Shen et al, , 2002Tandler et al, 2001;Stathis et al, 2002;Vernier et al, 2002), HCI and CSCW literature involving qualitative and quantitative studies focused on tabletop collaboration or single-user tabletop interaction, (e.g., Tang, 1991;Fitzmaurice, et al, 1999).…”
Section: The Impact Of Orientation On Collaborationmentioning
confidence: 99%
“…These explorations involved gathering data from a variety of sources including prior art HCI and CSCW literature describing existing digital tabletop systems, (e.g., Rekimoto and Saitoh, 1999;Streitz et al, 1999Streitz et al, , 2001; de Bruijn and RUSSELL KRUGER ET AL. Spence, 2001;Deitz and Leigh, 2001;Hancock and Booth, 2004;Shen et al, 2001Shen et al, , 2002Tandler et al, 2001;Stathis et al, 2002;Vernier et al, 2002), HCI and CSCW literature involving qualitative and quantitative studies focused on tabletop collaboration or single-user tabletop interaction, (e.g., Tang, 1991;Fitzmaurice, et al, 1999).…”
Section: The Impact Of Orientation On Collaborationmentioning
confidence: 99%
“…The familiar and lightweight action of touching a surface may also make it easier for people to take part in a social/public setting. User studies have shown how groups of people, new to tabletops, find it easy and enjoyable when sharing and assembling of sets of digital images for a variety of collaborative tasks (Huang & Mynatt, 2003;Ryall, Forlines, Shen & Morris, 2004;Scott, Grant & Mandryk, 2003;Shen, Lesh, Vernier, Forlines & Frost, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A number of tabletop systems have been designed to support image browsing and sharing. The Personal Digital Historian [21] is a tabletop penbased system that helps people construct, organize, navigate and share digital collections in an interactive multi-person conversational setting. SharePic [1] is a multitouch, gestural, and collaborative digital photograph sharing application for a tabletop, which was strongly influenced by the way physical photographs are handled and placed on physical tables.…”
Section: The Funky Coffee Tablementioning
confidence: 99%